Cultural Literacy in Academic-Related Documents of English Subject in Junior High School - Resti Amalia; M. Aries Taufiq (English Department FBS UNP, 2023)
This study investigated cultural literacy in academic-related documents of English subject in Junior high school. This study used content analysis. The data was words, phrases, clauses, sentences, and the pharaprashing of them taken from Junior High School. The finding showed that all the aspects of cultural literacy were stipulated in Indonesian government regulation. The similar condition applied to syllabus. Both of them were dominated by competency interpreting cultural context. However, there was no consistency across the documents because cultural literacy indicators appeared quite low in other documents such as lesson plan, learning material, and assessment. This condition indicated that students of Junior High School did not get any cultural literacy learning through English subject even though it was stipulated, and addressed in academic-related documents. This study proposed a possibility for teachers to insert cultural literacy for Junior High School students by introducing them to the classroom diversity.